Shoreline management experience, implications and actions : delegate information : Thursday 6 February 1997 at One Great George Street, Conference Centre, the Institution of Civil Engineers, London (Thomas Telford, 1997)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint seminar with MAFF held on 6 February 1997.